2021
DOI: 10.1016/j.heliyon.2021.e06740
|View full text |Cite
|
Sign up to set email alerts
|

The effect of substance use during pregnancy on neonatal outcomes in Ethiopia: A systematic review and meta-analysis

Abstract: Background Substance use during pregnancy mainly khat chewing (20%) and alcohol drinking (18.1%) are commonly practiced in Ethiopia. However, the effect of using these substances has not been studied nationally yet. Thus, this study was aimed to examine national evidence about the effect of substance use during pregnancy on birth outcome in the country, 2020. Methods Primary studies were accessed through Google scholar, HINARI, SCOPUS and PubMed databases. The methodolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 55 publications
1
10
1
Order By: Relevance
“…Although khat can lower the appetite and have vasoconstrictive effects on the placental blood vessels [25], no significant association was found between khat chewing and LBW neonates in the present study. This finding is contradictory to that reported earlier for LBW in Yemen [12,14,24,27] and Ethiopia [13,15,30]. Moreover, the frequency, pattern, and length of khat sessions showed no association with LBW in the present study.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Although khat can lower the appetite and have vasoconstrictive effects on the placental blood vessels [25], no significant association was found between khat chewing and LBW neonates in the present study. This finding is contradictory to that reported earlier for LBW in Yemen [12,14,24,27] and Ethiopia [13,15,30]. Moreover, the frequency, pattern, and length of khat sessions showed no association with LBW in the present study.…”
Section: Discussioncontrasting
confidence: 99%
“…LBW can result from several factors, including antenatal substance use [15]. The WHO Expert Committee on Drug Dependence (ECDD) declared that substance use during pregnancy may have adverse obstetric effects such as LBW and stillbirths [15,16]. The present study revealed that consanguinity was significantly associated with the delivery of LBW neonates by Yemeni pregnant women in Sana'a city, where mothers with LBW neonates were 3.7fold more likely to have consanguineous marriages compared to those with NBW neonates.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Investigating the use of other potential teratogens during pregnancy is also important [ 12 , 44 ]. Smoking and drinking are highly correlated; therefore, alcoholics are more likely to be heavy smokers [ 37 ].…”
Section: Teratogenicity Of Alcoholmentioning
confidence: 99%
“…Khat chewing during pregnancy has been associated with various obstetric, maternal, and child outcomes. A recent meta-analysis on the effects of various types of substance use on neonatal outcomes has demonstrated an association between prenatal khat use and low birth weight (LBW) and congenital anomalies (Bayih et al 2021). Furthermore, khat use has been reported to increase maternal mental distress and several obstetric complications such as pregnancyinduced hypertension, miscarriage, preterm labor, abruption of the placenta, and postpartum hemorrhage (Abdel-Aleem 2015; Nakajima et al 2017;Pinto et al 2010).…”
Section: Introductionmentioning
confidence: 99%